Kritik terhadap Pemikiran Aḥmad Khalâf Allâh tentang Kisah dalam al-Qurân - Lalu Supriadi (Islamica: Jurnal Studi Keislaman, 2013)
There have been many methods and ways to understand the message of the stories narrated in the Qurân, one of which being that which is introduced by the contemporary Muslim scholar named Aḥmad Khalâf Allâh. He is a specialist in the science of the story of the Qurân, as it were. This paper deals with this man and his new approach in understanding such story. It highlights the background of the man and the intellectual environment that forced him to offer his new approach. Speaking of stories in the Qurân as works of arts rather than as history, the man is considered unique in his own right. The paper slightly compares him to other scientists such as Muhammad Abduh, Fakr al-Dîn al-R?zî and al-Naysâbûrî and found that his approach is capable of addressing many problematic issues in the Qurân as far as stories are concerned, such as (1) the problem of inconsistence in the narration of the stories, (2) the notion of freedom of expression in the Qurân, and (3) the fact that the Qurân does entertain the idea of myth (asâtîr). The paper dwells into these three issues.